Involvement and skepticism towards the JCI Accreditation process among hospital's four sectors employees: suggestions for cultural change - Shiran Bord; Inna Sass; Gila Hayms; Kobi Moskowitz; Hagar Baruch; Fuad Basis (BMC, 2021)
Abstract Background Implementing the JCI Accreditation process as an organizational culture may face resistance. However, the skepticism and involvement of different hospital sectors (medical, nursing, paramedical, and administrative/logistic) in the process may vary. Conducting organizational change needs tools to decrease resistance. Objectives To investigate the attitudes, cultural norms, and satisfaction of the different sectors regarding the accreditation process, and to suggest ways to integrate the process as part of the organizational culture. Materials and methods A cross-sectional survey was conducted among 462 respondents (187 nurses, 95 physicians, 92 administrative, 88 paramedical) at Rambam Health Care Campus, a tertiary hospital in Israel. The hospital employees' attitudes, cultural norms, and satisfaction were assessed. ANOVA tests were used to examine the differences among the different sectors. The association between the satisfaction from the process and the preferred type of training was examined using Pearson's correlation coefficient. Results Significant differences were found among the sectors in the scores related to attitude, cultural norms, and satisfaction from the accreditation process (F (3, 456) = 17.95, p < 0.001, η2 = 0.10). Gabriel post-hoc test revealed significantly lower scores between the medical and paramedical sectors. A positive correlation was found between the degree of satisfaction with the process and the satisfaction with the training type. Frontal education and video demonstrations were rated significantly higher among all 10 training types. Conclusions More efforts should be made to increase involvement among physicians and paramedical teams in the accreditation process. Each sector leadership involvement is essential for their involvement too. Early involvement of the Israeli Medical Association in the process might have achieved better physicians' collaboration. Frontal education and video demonstrations may help decrease skepticism and increase positive attitudes.